The diagnostic value of pericardial aspiration at Groote Schuur hospital - Jennison, S H (Division of Cardiology, 2018)
In this MMed thesis I have reviewed retrospectively the pericardial aspirations performed between 1 July 1987 and 12th October 1989 at Groote Schuur Hospital, Cape Town. Documenting the reasons for aspiration, the complications of pericardiocentesis, and how cytologic, bacteriologic and biochemical examination of the aspirate influenced the clinicians' management of the 52 patients reviewed. The relatively low mortality of less than 2% is noted, in a procedure carried out for the relief of cardiac tamponade in 57% of the patients. A significant relationship between an ADA level higher than 51 international units per litre and a positive culture of mycobacterium tuberculosis from pericardial aspiration is demonstrated. The relatively low successful culture of mycobacterium tuberculosis (32% of the 29 patients clinically assessed as having tuberculous pericarditis) is noted, and recommendations to improve the yield from culture are made.